Mequindox induces apoptosis, DNA damage, and carcinogenicity in Wistar rats. (May 2019) - Liu, Qianying; Lei, Zhixin; Gu, Changqin; Guo, Jingchao; Yu, Huiru; Fatima, Zainab; Zhou, Kaixiang; Shabbir, Muhammad A.B.; Maan, Muhammad Kashif; Wu, Qinghua; Xie, Shuyu; Wang, Xu; et al.
Abstract: Mequindox (MEQ) is a synthetic antibacterial agent. Recent studies showed that MEQ and its primary metabolites exhibit strong genotoxicity to mammalian cells, and MEQ induced carcinogenicity in mice. These findings suggest that chronic exposure to MEQ could lead to an increased risk of cancer later in life. In the present study, four groups of Wistar rats (55 rats/sex/group) were fed with diets containing MEQ (0, 25, 55, and 110 mg/kg) for 2 years. The results showed that the hematological system, liver, kidneys, and adrenal glands, as well as the developmental and reproductive systems, were the main targets for MEQ. Liver toxicity mediated by MEQ was associated with apoptosis and the nuclear factor κB (NF-κB) signaling pathway. In addition, MEQ increased the incidence of tumors in rats. Phosphorylated histone H2AX (γ-H2AX) is identified as a biomarker of cellular response to DNA double-strand breaks (DSB). Our data demonstrated that γ-H2AX expression was significantly increased in tumors. Thus, high levels of DSB might be responsible for carcinogenesis in rats, and further investigation is absolutely required to clarify the exact molecular mechanisms for carcinogenicity caused by MEQ in vivo . Highlights: A two - year carcinogenicity study of MEQ in rats. MEQ increased the incidence of tumors in rats. γ-H2AX formation in the tumors induced by MEQ. MEQ induced apoptosis and activated NF-κB pathway in the liver. MEQ is a genotoxic carcinogen in rats.